Compressive and flexural strength of coal bottom ash lightweight concrete - David, Thevaneyan Krishta; Krishnamoorthy, Renga Rao; Sivarao, Subramonian; Ramesh, S. (2023)
Environmental degradation, climate change, and pollution are the three major environmental issues. The high cost of traditional building materials is a major element determining the price of residential houses in Malaysia. One of the best strategies to achieve environmental sustainability in building construction is to use waste materials, particularly lightweight concrete, which can lessen the stress on structural elements. This may help to reduce the cost of structural building when compared to traditional concrete. As a result of these two important contributions, the goal of this research is to determine the ability of lightweight concrete (LWC) with coal bottom ash (CBA) as a partial cement substitute in compressive and flexural strength tests. The replacement rate of CBA as a variable parameter was modified in this study at 5%, 10%, and 15% of cement weight. Concrete's compressive and flexural strength is determined at 7, 14, and 28 days of age. The partial substitution of CBA in concrete has good potential in terms of construction cost and environmental sustainability, according to this study.